Regulation of sensory perception and motor abilities by brain-specific action of chromatin remodeling factor CHD1 - Schoberleitner, Ines; Mertens, Birte; Bauer, Ingo; Lusser, Alexandra (Frontiers in Molecular Neuroscience, 2022)
The ATP-dependent chromatin remodeling factor CHD1 (chromodomain-helicase-DNA binding protein 1) is involved in both the de novo assembly and the remodeling of chromatin. Recently, we discovered a crucial role of CHD1 in the incorporation of the histone variant H3.3 in the fly brain illustrated by widespread transcriptional upregulation and shortened lifespan in Chd1-mutant animals. Because many genes linked to sensory perception were dysregulated in Chd1-mutant heads, we studied the role of CHD1 in these processes. Here we show that Chd1-mutant flies have severe defects in their response behavior to olfactory and gustatory but not visual stimuli. Further analyses suggested that poor performance in gustatory response assays was caused by reduced motivation for foraging and feeding rather than defects in taste perception. Moreover, we show that shortened lifespan of Chd1-mutant flies is accompanied by indications of premature functional aging as suggested by defects in negative geotaxis and exploratory walking assays. The latter phenotype was rescued by neuronal re-expression of Chd1, while the olfactory defects were not. Interestingly, we found evidence for indirect regulation of the non-neuronal expression of odorant binding proteins (Obp) by neuronal expression of Chd1. Together, these results emphasize the crucial role of CHD1 activity controlling diverse neuronal processes thereby affecting healthy lifespan.